Testing for unit roots and granger non-causality in time series with multiple structural breaks. An international stock markets application - Buzzi, Sergio Martín (2014)
Fil: Buzzi, Sergio Martín. Universidad Nacional de Córdoba. Facultad de Ciencias Económicas; Argentina.